Artificial Chromosome Doubling in Allotetraploid Calendula officinalis - Esmaeili, Ghasem; Van Laere, Katrijn; Muylle, Hilde; Leus, Leen (Frontiers in Plant Science, 2020)
Calendula officinalis L. is known as an ornamental plant as well as a source of biochemical compounds used in cosmetics and industry. C. officinalis has a complex karyotype. Published chromosome numbers differ between 2n = 4x = 28 or 32. We have estimated genome sizes in nine commercial cultivars and evaluated the ploidy level by karyotyping and Fluorescent In Situ Hybridization (FISH) using 5S and 45S rDNA loci. The detection of chromosome sets of two rather than four homologues clearly revealed that C. officinalis has an allotetraploid background. In addition, four signals for 45S but only two for 5S were found by using FISH. Artificial chromosome doubling is a common technique in plant breeding, as polyploidization results in several consequences for plant growth and development. Especially the allotetraploid background in C. officinalis is interesting when examining the effect of chromosome doubling on the plant phenotype. Here we describe chromosome doubling of three allotetraploid cultivars of C. officinalis, ‘Nova’, ‘1557-3’ and ‘Orange Beauty’. Three antimitotic agents - colchicine, oryzalin and trifluralin - were used in different concentrations to find the combination of the best agent and the best dosage to obtain octaploids. For all three cultivars a few octaploids were obtained. A concentration of 200 and 400 ppm of colchicine was most efficient for chromosome doubling in ‘Nova’ and ‘Orange Beauty’, respectively. For ‘1557-3’ the treatment with 20 ppm oryzalin was also effective. Cell numbers and first observations of the phenotype in the chromosome doubled plants show thicker leaves and bigger cells, as commonly observed after ploidy doubling. Due to the low number of chromosome doubled plants obtained and More elaborate phenotyping will be performed on following generations cultivated under field conditions.